Human Rights and Digital Health Technologies - Nina Sun; Kenechukwu Esom; Mandeep Dhaliwal; Joseph J. Amon (Harvard FXB Center for Health and Human Rights, 2020)
Digital health technologies have been heralded as a critical solution to challenges and gaps in the delivery of quality health care and essential to achieving the Sustainable Development Goals. Yet they also present threats to privacy and confidentiality, which can lead to discrimination and violence, resulting in violations of the rights to health, housing, employment, freedom of assembly, expression, protection from arbitrary detention, bodily autonomy, and security. More broadly, without proper planning and safeguards, digital health technologies can contribute to expanding health inequity, widening the "digital divide" that separates those who can and cannot access such interventions. This article outlines key harms related to digital technologies for health, as well as ethical and human rights standards relevant to their use. It also presents several strategies for mitigating risks from digital health technologies and reviews mechanisms of accountability, including recent judicial rulings.